2015
DOI: 10.1016/j.jbiomech.2015.02.040
|View full text |Cite
|
Sign up to set email alerts
|

Transition from fetal to neonatal circulation: Modeling the effect of umbilical cord clamping

Abstract: Hemodynamics of the fetal to neonatal transition are orchestrated through complex physiological changes and results in cardiovascular adaptation to the adult biventricular circulation. Clinical practice during this critical period can influence vital organ physiology for normal newborns, premature babies and congenital heart defect patients. Particularly, the timing of the cord clamping procedure, immediate (ICC) vs. delayed cord clamping (DCC), is hypothesized to be an important factor for the transitory feta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 52 publications
2
27
0
Order By: Relevance
“…He proposed that the sudden rise in cerebral circulation was the underlying mechanism for the higher incidence of intraventricular hemorrhage after early cord clamping (ECC) in preterm neonates. Our computer simulation of transitional circulation supports Hofmeyr’s finding (3). The simulation demonstrates that a sudden rise in cerebral pressure and blood flow is inevitable if the placental circulation is closed before the increase in pulmonary blood flow has occurred as a result of respiration.…”
supporting
confidence: 89%
“…He proposed that the sudden rise in cerebral circulation was the underlying mechanism for the higher incidence of intraventricular hemorrhage after early cord clamping (ECC) in preterm neonates. Our computer simulation of transitional circulation supports Hofmeyr’s finding (3). The simulation demonstrates that a sudden rise in cerebral pressure and blood flow is inevitable if the placental circulation is closed before the increase in pulmonary blood flow has occurred as a result of respiration.…”
supporting
confidence: 89%
“…DCC improves blood pressure, reduces the need for blood transfusions and the risk of intra-ventricular haemorrhage and necrotizing enterocolitis in preterm infants [9]. Furthermore, DCC maintains oxygenation by sustained placental circulation and is beneficial if spontaneous pulmonary respiration is delayed or impaired [10][11][12][13]. Recently the use of the term 'deferred' cord clamping has been recommended as this suggests a planned policy in contrast to the term 'delayed' cord clamping which may imply that the cord is clamped later than the ideal time [14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that a 1–3 minute DCC can significantly impact a newborn’s hemodynamics, mainly due to the improved blood volume and the sustained placental respiration. 2 …”
mentioning
confidence: 99%